Multi-cultural technology or product development through the iterative analysis and synthesis of technology components - Martinez, Iris Ann (ASEAN engineering journal)
Technology transfer has become a common practice of countries and organizations to acquire technology. Aside from enabling less advanced countries or organizations to acquire technology for economic advancement, a significant advantage of technology transfer is that it enables advanced countries to outsource their internal Research and Development (R&D)....